Hábitos alimenticios de la zorra gris Urocyon cinereoargenteus (Carnivora:Canidae) en la región meridional de Baja California, México - Arnaud, Gustavo (Universidad de Costa Rica, 1990)
Food habits of gray fox (Urocyon cinereoargenteus) from the meridional region of Baja California were determined from scats (N=IOI) collected from May 1986 through April 1987. Frequency of ocurrence of major food items found in scats for all seasons were rodent -Peognathus - (45.5%), rabbit -Sylvilagus- (27.7%), birds (10.8%), mylipeds (10.8%), and gramineae (10.8%). We can conclude that this carnivore is a generatist feeder